Estoppel and Substantive Legitimate Expectation in South African Tax Law - Du Toit, Genevieve (Department of Commercial Law, 2014)
The purpose of this dissertation is to explore the legal avenues that may be open to taxpayers for holding the South African Revenue Services ('SARS') to the representations which it makes to the public in the form of general statements and specific rulings or directives. These avenues lie in two areas of law, namely the doctrine of estoppel as it has been developed in a public law context, and (potentially) the realm of so-called substantive legitimate expectation.